Is Having Urban Green Space in the Neighborhood Enough to Make a Difference? Insights for Healthier City Design - Bressane, Adriano [UNESP]; Ferreira, Maria Eduarda Guedes [UNESP]; da Silva Garcia, Ana Júlia [UNESP]; de Castro Medeiros, Líliam César [UNESP] (MDPI, 2024)
Background: Prior research indicates that engagement with nature is associated with mental well-being; however, the impact of accessibility to urban green spaces (UGS) with suitable infrastructure for visitation and physical activities, like leisure or recreation, remains underexplored, particularly in developing countries. Purpose: This study delves into whether merely having green space in the neighborhood is sufficient to impact residents' mental health in Brazilian metropolitan regions. Method: Utilizing a cross-sectional survey, data were collected from 2136 participants. The analyzed variables included the intensity, duration, and frequency of nature engagement, suitability of UGS for visitation and physical activities, and mental well-being indicators measured by the DASS-21 scale. Multivariate statistical analyses and multiple regression models were employed to verify hypothetical relationships. Results and conclusions: Higher intensity, duration, and frequency of nature engagement in UGS were significantly associated with lower depression, anxiety, and stress scores. Notably, having urban UGS in the neighborhood alone was not enough to reduce mental health issues. Practical implications: The findings point out the need for urban planning policies that prioritize the development of high-quality, accessible green spaces to maximize mental well-being benefits. These insights could inform city designs that foster healthier urban environments. Future directions: Longitudinal studies are needed to establish causality between nature engagement and mental health improvements. Further research should incorporate objective measures of nature engagement and explore more aspects of green space quality, such as biodiversity and amenities.